2023
DOI: 10.1186/s12944-022-01761-4
|View full text |Cite|
|
Sign up to set email alerts
|

The predictive value of nontraditional lipid parameters for intracranial and extracranial atherosclerotic stenosis: a hospital-based observational study in China

Abstract: Background Ischemic strokes are primarily caused by intracranial and extracranial atherosclerotic stenosis. Nontraditional lipid parameters broaden traditional lipid profiles, better reflect the metabolism and interaction between different lipid components, and optimize the predictive ability of lipid profiles for atherosclerotic diseases. This research was carried out to investigate the predictive value of nontraditional lipid parameters for intracranial or extracranial atherosclerotic stenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Further investigation is warranted to determine if AIP levels can serve as a marker for Pre-DM and DM. Recent research has explored the association between AIP and cerebrovascular disease, revealing that higher AIP levels are correlated with a higher incidence of atherosclerotic stenosis in the carotid and intracranial arteries [ 10 , 32 ]. In the general population, increased baseline and cumulative AIP levels are associated with a greater risk of ischemic stroke [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation is warranted to determine if AIP levels can serve as a marker for Pre-DM and DM. Recent research has explored the association between AIP and cerebrovascular disease, revealing that higher AIP levels are correlated with a higher incidence of atherosclerotic stenosis in the carotid and intracranial arteries [ 10 , 32 ]. In the general population, increased baseline and cumulative AIP levels are associated with a greater risk of ischemic stroke [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIP potentially serves as a significant predictor of intracranial arterial stenosis, the risk of ischemic stroke, and poor stroke outcomes. [9][10][11][12]. On the other hand, AIP serves as a reliable indicator of IR, which indicates that it may differentiate stroke risk in individuals with abnormal glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Previous observational studies have indicated that LCI was an independent predictor of coronary artery disease severity and progression; [20][21][22]54,55 additionally, in recent reports by Yu et al, LCI was also found to effectively predict atherosclerotic stenosis in both intracranial and extracranial arteries. 19 However, no studies have yet evaluated the association between LCI and NAFLD. In our current study, using health examination data from a general population, we compared the association of LCI and traditional lipid parameters with NAFLD and assessed their diagnostic abilities using ROC curves.…”
Section: Discussionmentioning
confidence: 99%
“…Completed studies have shown that LCI can effectively identify and predict the risk of atherosclerosis and cardiovascular diseases. [19][20][21][22] In fact, as a comprehensive indicator for lipid profile assessment, the various components of the LCI are highly correlated with NAFLD. 8,23 Compared to traditional single lipid markers, the LCI may better reflect the multidimensional lipid metabolism abnormalities associated with the development of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…As a robust biomarker of dyslipidemia, AIP has been considered to be a powerful independent predictor of adverse cardiovascular and cerebrovascular events. AIP is potentially served as a signi cant predictor of intracranial arterial stenosis, the risk of ischemic stroke, and poor stroke outcomes (8)(9)(10)(11). On the other hand, AIP serves as a reliable indicator of insulin resistance, which indicates that it may differentiate stroke risk in individuals with abnormal glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%